Studi Kinerja Pegawai Negeri Sipil di Kelurahan Wenang Selatan - Rotinsulu, Jimmy Charles Esau; Goni, John Hein (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The purpose of this study was to describe the performance of employee at the South Wenang Sub-District in Wenang District Manado City. The methodology used in this study was a qualitative research. Data were collected through direct interview and field observations. Informants obtained by the criterion that they can provide the information required in this study, namely the South Wenang Village office staff totaling five people, consisting of 4 persons who occupy positions of structural, nonstructural 1 employees (staff employees) and 6 members of the public , composed of community leaders, religious leaders, and members of the general public. The results showed that how the employee is optimal according to SOP. This could be seen from the work that was done independently according to the main duty and function of the employee. The use of working hour of the employee was optimal. This could be seen from the final job performance in accordance to the specified working hours. The work behavior of the South Wenang Sub-District employee was optimal. It signified by the motivation and discipline of the employee in carring out their duty. The target achievement of the employee was optimal. It was Â signify by the realization of the defined task objectives. The officialsâ€™ performance (the leader and staff) have showed a good result in accordance with the main job and function. This achievement be maintained and improved with a better re-establishment of formal study or technical training, also with the supported environment apparatus and working spirit. Key Word : performance, employee